The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/jocc.12030
|View full text |Cite
|
Sign up to set email alerts
|

Attachment, Acculturation, and Psychosomatic Complaints Among Hispanic American University Students

Abstract: This study investigated adult attachment and acculturation frameworks of reported psychosomatic complaints related to perceived discrimination among a sample of Latino/Hispanic university students (N = 160). The model supported by the data suggests that attachment anxiety, acculturation toward the dominant cultural norms, and adherence to Latino/Hispanic cultural beliefs are important factors for perceived discrimination and psychosomatic complaints experienced by Latino/Hispanic students. Counseling implicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…Specifically, Latinx American college students with high attachment avoidance tend to experience negative mood, show poor adjustment (Wei et al, 2004), and low levels of well-being (Garriott et al, 2010). Similarly, Latinx participants with high attachment anxiety are more likely to experience lower levels of well-being (Garriott et al, 2010) and greater somatic complaints (Wang et al, 2016). It is important to note that Mexican/Latinx individuals reported higher attachment anxiety and avoidance than White individuals, and that Mexican individuals endorsed higher attachment avoidance than their U.S. Latinx counterparts (Schmitt et al, 2004).…”
Section: Cross-cultural Adult Attachmentmentioning
confidence: 99%
“…Specifically, Latinx American college students with high attachment avoidance tend to experience negative mood, show poor adjustment (Wei et al, 2004), and low levels of well-being (Garriott et al, 2010). Similarly, Latinx participants with high attachment anxiety are more likely to experience lower levels of well-being (Garriott et al, 2010) and greater somatic complaints (Wang et al, 2016). It is important to note that Mexican/Latinx individuals reported higher attachment anxiety and avoidance than White individuals, and that Mexican individuals endorsed higher attachment avoidance than their U.S. Latinx counterparts (Schmitt et al, 2004).…”
Section: Cross-cultural Adult Attachmentmentioning
confidence: 99%
“…A strong sense of cultural and personal identity helps emerging adults develop self-esteem and resilience (Hipolito-Delgado, 2016;Schwartz et al, 2009). Research has found that although Latino college students with a secure ethnic identity perceived discrimination more frequently, their secure ethnic identity assisted them in coping with and managing responses to discriminatory events (Hipolito-Delgado, 2016;Wang, Scalise, Barajas-Munoz, Julio, & Gomez, 2016). In addition, a strong sense of cultural identity aids emerging adults from internalizing symptoms such as depression and anxiety (Schwartz et al, 2009).…”
Section: Acculturative Stress Of Recent Latino Immigrantsmentioning
confidence: 99%
“…In addition, the frequent messages immigrants receive about being unwelcome may make it hard for them to be proud of their ethnic background. A large number of young adults perceive regular discrimination in their lives, and the predisposition to internalize discriminatory events relates to their stage of ethnic identity development (Hipolito-Delgado, 2016;Wang et al, 2016). Meyer (2003) described the effects of exposure to discrimination as minority stress, or "the excess stress to which individuals from stigmatized social categories are exposed as a result of their social, often a minority, position" (p. 675).…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Although immigrants in the United States come from diverse cultural backgrounds, they share similar experiences of being newcomers and having to acculturate to a new environment (Choi et al, 2019; C. D. Wang et al, 2016). Additionally, because more than two thirds of immigrants in the United States come from countries where collectivistic cultural values are the norm, with a strong emphasis on family loyalty and obligation (Pew Research Center, 2015), college students from immigrant families are likely brought up with different communication and relationship‐maintenance patterns from those typically seen in the United States (C. D. Wang et al, 2016). Thus, it is important to better understand the long‐term effects of having to navigate different cultural norms on college students from immigrant families.…”
mentioning
confidence: 99%